ChemInform Abstract: Prediction of Acidity Constants of Some Important Selenium Oxoacids in Aqueous Solution by Computational Techniques. Issue 26 (1st July 2014) - Abedi, Mostafa; Farrokhpour, Hossein; Farnia, Solaleh
Abstract The acidity constants (pKa) of two important series of selenium oxoacids including H2SeOn (n = 1‐5) and H2Se2On (n = 1, 3, 4, 6 and 7) are predicted by two different computational methods.